LEVANTAMENTO BOTÃ‚NICO DAS PLANTAS INVASORAS EM CULTURA DE ARROZ (ð˜–ð˜³ð˜ºð˜»ð˜¢ ð˜´ð˜¢ð˜µð˜ªð˜·ð˜¢ L.) IRRIGADA - Rochelle, Luiz Antonio; Banzatto, Nicolau Victorio; Delistoianov, JoÃ£o (REVISTA DE AGRICULTURA, 2020)
LEVANTAMENTO BOTÃ‚NICO DAS PLANTAS INVASORAS EM CULTURA DE ARROZ (ð˜–ð˜³ð˜ºð˜»ð˜¢ ð˜´ð˜¢ð˜µð˜ªð˜·ð˜¢ L.) IRRIGADA